Improved QuEChERS and solid phase extraction for multi-residue analysis of pesticides in paddy soil and water using ultra-high performance liquid chromatography tandem mass spectrometry - Zaidon, Siti Zulfa; Ho, Yu Bin; Mohamad Hamsan, Hazwanee; Hashim, Zailina; Saari, Nazamid; Praveena, Sarva Mangala (Elsevier, 2019)
Two new sensitive and selective methods were developed to quantify thirteen pesticides in soil and water. The method developed in soil was optimized and modified based on the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuECHERS) procedure, followed by a dispersive solid phase extraction (dSPE) clean-up technique. The method developed in the water samples was based on glass fiber and nylon filtration, followed by the solid phase extraction (SPE) clean-up technique. Both methods used ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) for analysis. The developed method showed good linearity at calibration points ranging from the instrumental quantification limit (IQL) to 500 ng mL−1, and the correlation coefficients (R2) for all of the target analytes were higher than 0.9990. The method showed recoveries ranging from 74% to 111% in soil and 77% to 117% in water. The method detection limit (MDL) for all of the target analytes ranged from 0.03 ng g−1 to 0.4 ng g−1 in soil and 0.1 ng L−1 to 10 ng L−1 in water. Both methods were applied to field paddy soil and water samples to quantify pesticide residues in the samples. Isoprothiolane was the highest concentration pesticide in paddy soil (34.81 ng g−1), whereas chlorantraniliprole (11.83 ng mL−1) was the highest concentration pesticide in the paddy water sample. Based on the instrument and method performance validation results, the developed methods can be applied as part of pesticide residue analysis in environmental and agricultural matrices, thus aiding in regulating and monitoring pesticide usage in agricultural fields.